Therapeutic Aspects in Shalawatan Tradition (An Ethnographic Study on Shalawatan Communities in Banyumas) - Muskinul Fuad (Postgraduate Program, State Institute on Islamic Studies Purwokerto, 2017)
This study aims to reveal and identify therapeutic aspects in the tradition of shalawatan in Banyumas area. With ethnographic approach, this study describe the various aspects of therapeutic in the tradition of shalawatan. It can consider the elements that exist in the shalawatan, namely the shalawat reading or dzikir, the relationship between the leader (habib) and its members, the atmosphere of relations among its members, and the speech content (taushiyah) of habib or kiyai. The substance that be presented is the psychological implications caused by individual rituals and experiences in performing solawatan tradition. The therapeutic aspect is essentially part of this study. There are many therapeutic aspects of shalawatan tradition that have been revealed in this research, namely auto-suggestion, togetherness, psycho-spiritual and group therapy. The next study can find other ones, for example the aspect of musical of shalawatan that sharpens the sense or the religious emotions of the doers, so as not to dry in practice religious teachings. In addition there is also a scientific aspect that is contained in the moment of giving tausiyah (mau’idzah hasanah) by habib and kiyai in a shalawatan forum, which helps the jama’ah to develop positive thoughts in life. Similarly,, aspects of self-actualization development, the process of self imitation (identification), and aspects of religious transformation that exist in the subjective experience of the perpetrators of shalawatan